Activity of PD-1 Inhibitor Combined With Anti-Angiogenic Therapy in Advanced Sarcoma: A Single-Center Retrospective Analysis - You, Yang; Guo, Xi; Zhuang, Rongyuan; Zhang, Chenlu; Wang, Zhiming; Shen, Feng; Wang, Yan; Liu, Wenshuai; Zhang, Yong; Lu, Weiqi; Hou, Yingyong; Wang, Jing; et al. (Frontiers in Molecular Biosciences, 2021)
Although immune-checkpoint-inhibitors (ICIs) have been deeply explored in various of cancer types including soft tissue sarcomas (STS). Anti-VEGF receptor tyrosine-kinase inhibitors (TKIs) combine with ICIs shown antitumor activity in patients with alveolar soft-part sarcoma (ASPS). However, they have not been well understood in other STS subtypes, such as leiomyosarcoma (LMS), dedifferentiated liposcarcoma (DDLPS), undifferentiated pleomorphic sarcoma (UPS) and In this retrospective study, we collected 61 patients were diagnosed as advanced STS based on the imaging and histology, including LMS, DDPLS and UPS etc. Among of them, 41 patients were treated with ICIs combine TKIs and 20 patients received ICIs therapies. The endpoints of progression-free survival (PFS) and objective response rate (ORR) were analyzed in two groups, and overall response of each patient with partial response (PR), stable disease (SD) and progressive disease (PD).In total of the 61 patients with STS, including LMS (n = 20), DDLPS (n = 17), UPS (n = 8), ASPS (n = 7), MFS (n = 7) and AS (n =2). Our results showed that the median PFS (mPFS) was significant prolonged in ICIs in combination with TKIs group (11.74 months, 95% CI 4.41-14) compared with ICIs group (6.81 months, 95% CI 5.43-NA) (HR 0.5464, p = 0.043). The 12-month PFS rate of patient received ICIs in combination with TKIs was increased from 20.26% (95% CI 0.08-0.53) to 42.90% (95% CI 0.27-0.68). Among the combination therapy group, 12 patients (30%) achieved PR, 25 patients (62.5%) achieved SD and 3 patients (7.5%) achieved PD maintain more than 3 months or longer. Among the non-TKI-combination group, 2 patient (9.5%) achieved PR, 14 patient (66.7%) achieved SD and 5 patient (23.8%) achieved PD within 3 months. The ORR in two groups were 30.0% (ICIs combined with TKIs group) and 9.5% (ICIs group), respectively. A notable ORR was observed in ICIs and TKIs combination groups, especially ASPS (66.7%), MFS (42.9%) and UPS (33.3%) STS subtypes. The PD-L1 expression and tumor burden (TMB) were determined in each patient. This study suggested that ICIs combined with TKIs have antitumor activity in patients with STS, particularly in ASPS and MFS subtypes.